HUBUNGAN KUALITAS MIKROBIOLOGI AIR BAKU DAN HIGIENE SANITASI DENGAN CEMARAN MIKROBA PADA AIR MINUM ISI ULANG DI KECAMATAN TEMBALANG - Endang Sri Utami; Martini Martini; Lintang Dian Saraswati; Susiana Purwantisari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Based on Indonesian Health Ministry regulation No. 492/ MENKES/PER/ IV/2010, the MPN coliform dan E.coli of drinking water should be 0 of 100 mL sample. A previous research showed that 95% of samples did not require the microbiological contamination. The research aimed to analyze the correlation between microbiological quality of raw water and hygiene sanitation with microbiological contamination of refilled drinking water. The type of this research is analytic with cross sectional approach. The samples are 47 depots and 55 workers. The results showed that 85.1% of samples did not require the microbiological contamination. Using by Chi-square test analysis (α=5%)  indicates that the personal hygiene has p=0.035 (OR=10,000 and CI=1.095 to 91.309). It means personal hygiene have a correlations with microbiological contamination of refilled drinking water. While the microbiological quality of the raw water (p=0.188), the conditions of depots sanitary (p=0.999), the conditions of equipment sanitary (p=0.410) were not associated with the contamination of refilled drinking water. Therefore, it is necessary to optimize the sanitary inspection and testing the sampels frequently. Also, socialization for depot’s workers is needed to increase the hygiene sanitation.